TRAINING ON MAKING HYDROPONIC MEDIA FROM ORGANIC WASTE FOR SUPPORTING COMMUNITIES IN PAYA GABOH - muliana muliana; Yusra; Jamilah; Muhammad Yusuf N (Global Science Society, 2022)
Gampong (village) Paya Gaboh is a village located in Sawang District, North Aceh Regency. The people has activities as farmers, a small part of traders, craftsmen, civil servants, entrepreneurs and others. Most of the people of Paya Gaboh Village live in a housing complex with a small yard. A limited yard if used optimally will be profitable. Hydroponic technology is a solution for people who have limited yards. The success of hydroponic technology is highly dependent on knowledge and skills. Hydroponic activist must know the media for hydroponics to be profitable. The Team from the Faculty of Agriculture Malikussaleh University carried out training on making hydroponic growing media from organic waste for the Community of Paya Gaboh Village Nisam District, North Aceh Regency. The aim is to transfer knowledge and skills on how to make and use growing media for hydroponics from insitu organic waste (rice husks and coconut husks). The method was to an agreement between the implementing team and the village head and the community in Gampong Paya Gaboh, then the community is given knowledge and training: how to hydroponic building design, create a growing medium, sow seeds, made and used nutrients and how to plant with a hydroponic system. The results of the training showed that the participants were very enthusiastic and very serious about participating in the training and demonstrating how to implement it step by step. Some communities have implemented planting with a hydroponic system as obtained during the training.